Forest elephant surveys in Central Africa - Richard Barnes (Pachyderm)
Summarizes results from a ground reconnaissance survey intended to extrapolate forest elephant numbers in suitable Central African forest habitats. It is suggested that about 225,000 forest elephant may be present in Central African forests: one third in Gabon which are not seriously threatened from ivory poaching, one third in Cameroon, Congo and Central African Republic which are declining fairly rapidly.and the remainder in Zaire which are swiftly disappearing.